Serum beta hCG in early second trimester as a predictor of gestational hypertension - Rajesh, Aparna; Muralidharan, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive disorders of pregnancy complicate upto 10% of pregnancies worldwide, and constitute one of the greatest causes of maternal and perinatal morbidity and mortality. The goal of this study is to evaluate the serum beta hCG levels in pregnant women as a predictor of gestational hypertension. Methods: This is a prospective study done at K. S. Hegde Medical Academy during the month of November 2015 to January 2017. Serum beta hCG was estimated between 14-20 weeks of gestation in 90 women with singleton pregnancy irrespective of parity. Regular follow up of the cases were done till delivery. Results were analysed statistically. Results: Out of 90 women, 81 women were followed till term and 12 (14.8%) cases developed gestational hypertension. β HCG levels (Mean±SD) were higher (69808.66±54764.7 vs. 38126.49±97419.2; p<0.28) in subjects who developed gestational hypertension. Serum beta hCG (median >32726 mIU/ml) has a sensitivity of 75%, specificity of 72.5% and accuracy of 72.8%. Conclusions: Our study indicate an increased risk of gestational hypertension in women with elevated levels of serum beta hCG. As yet there are no practically acceptable and reliable screening tests for gestational hypertension, serum beta hCG seems to be good noninvasive early predictor for the development of gestational hypertension.